Resistance of Subtype C HIV-1 Strains to Anti-V3 Loop Antibodies. (2nd April 2012) - Almond, David; Krachmarov, Chavdar; Swetnam, James; Zolla-Pazner, Susan; Cardozo, Timothy
Abstract : HIV-1's subtype C V3 loop consensus sequence exhibits increased resistance to anti-V3 antibody-mediated neutralization as compared to the subtype B consensus sequence. The dynamic 3D structure of the consensus C V3 loop crown, visualized by ab initio folding, suggested that the resistance derives from structural rigidity and non- β -strand secondary protein structure in the N-terminal strand of the β -hairpin of the V3 loop crown, which is where most known anti-V3 loop antibodies bind. The observation of either rigidity or non- β -strand structure in this region correlated with observed resistance to antibody-mediated neutralization in a series of chimeric pseudovirus (psV) mutants. The results suggest the presence of an epitope-independent, neutralization-relevant structural difference in the antibody-targeted region of the V3 loop crown between subtype C and subtype B, a difference that we hypothesize may contribute to the divergent pattern of global spread between these subtypes. As antibodies to a variable loop were recently identified as an inverse correlate of risk for HIV infection, the structure-function relationships discussed in this study may have relevance to HIV vaccine research.